PENGARUH ONLINE MARKETING TERHADAP MINAT BELI YANG DIMEDIASI OLEH TRUST PADA MAHASISWA DI UNIVERSITAS MATARAM (KASUS PENGGUNAAN INSTAGRAM SEBAGAI MEDIA ONLINE MARKETING) - Prayoga, Dwi Widhy (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2017)
This research is aimed at determining and analyzing the effect of online marketing using Instagram on the trust, effect of online marketing in the Instagram on the online buying interest, the effect of online marketing in Instagram on the online buying interest mediated by trust. This research is associative study using primary and secondary data sources. The data were collected through questionnaires, interview, and documentation. The population of this research are 100 students of Mataram University using Instagram media. The samples ere selected through purposive sampling. The analysis is using PLS.The research showed that online marketing had positive and significant effect on the buying interest, online marketing had positive and significant effect on the trust, trust had positive and significant effect on the buying interest, online marketing had positive and significant effect on the trust through mediation. This research suggested that online selling throughÂ  Instagram shouldÂ  improve the service though online marketing, the seller should describe clearly the profile of online store such the long year of selling, not in private web, and should explain the detail of mechanism of payment to show that the seller is responsible on the online store.Keywords: online marketing, trust, buying interest, Instagram, partial least square